2014
DOI: 10.1016/j.newast.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Optical polarization observations with the MASTER robotic net

Abstract: We present results of optical polarization observations performed with the MASTER robotic net for three types of objects: gamma-ray bursts, supernovae, and blazars. For the Swift gamma-ray bursts GRB100906A, GRB110422A, GRB121011A, polarization observations were obtained during very early stages of optical emission. For GRB100906A it was the first prompt optical polarization observation in the world. Photometry in polarizers is presented for Type Ia Supernova 2012bh during 20 days, starting on March 27, 2012. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…Results of polarization measurements of GRB 100906A, GRB 110422A, and GRB 121011A by MASTER have been reported by Gorbovskoy et al (2012);Pruzhinskaya et al (2014). For GRB 100906A, from 0.01 to 0.19 h after T0, it was found that the time-averaged dimensionless Stokes parameter was less than the standard deviation of that of the field stars (2 per cent for that case).…”
Section: Results Of Master Polarization Measurementsmentioning
confidence: 66%
See 1 more Smart Citation
“…Results of polarization measurements of GRB 100906A, GRB 110422A, and GRB 121011A by MASTER have been reported by Gorbovskoy et al (2012);Pruzhinskaya et al (2014). For GRB 100906A, from 0.01 to 0.19 h after T0, it was found that the time-averaged dimensionless Stokes parameter was less than the standard deviation of that of the field stars (2 per cent for that case).…”
Section: Results Of Master Polarization Measurementsmentioning
confidence: 66%
“…Thus, one MASTER telescope, when observing alone, is able to measure one Stokes parameter. Details on the Stokes parameter derivation and the calibration of polarization measurements are given in Pruzhinskaya et al (2014). The differences between the signals obtained by MASTER-Tunka in two polarizers for the time interval from 202.8 to 315.7 s yield the dimensionless time-averaged Stokes parameter Q = 2.4 ± 2.5 per cent.…”
Section: Photometrymentioning
confidence: 99%
“…The MASTER robotic telescopes 1 are a network of identical instruments deployed over several continents and equipped with identical CCD cameras capable of performing B,V,R J ,I (Johnson/Bessell) photometric and linear polarimetric observations (Lipunov et al 2010;Kornilov et al 2012;Pruzhinskaya et al 2014). Each MASTER-II observatory has twin 0.40-m f/2.5 wide field reflectors (Hamilton design; see Kornilov et al (2012)) and a prime focus 4k x 4k CCD camera, which provide a total 8 square-degree field and reaches to a white-light magnitude of 20-21 (in 180s exposure).…”
Section: Master Global Robotic Network Observationmentioning
confidence: 99%
“…The technique of polarimetric measurements used on MASTER network telescopes is considered in detail in (Pruzhinskaya et al 2014). It allows detecting the linear polarization at 1-2% level for objects brighter then 14mag.…”
Section: Master Global Robotic Network Observationmentioning
confidence: 99%
See 1 more Smart Citation